2008
DOI: 10.1007/s00213-007-1059-6
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in schedule-induced polydipsia and the role of gabaergic and dopaminergic systems

Abstract: These data provide novel evidence that individual differences in SIP are not predictive of behavioral reactivity in animal models of anxiety and suggest an important role for the dopaminergic system in such individual differences. These findings point to SIP as a useful animal model for investigating the neurobiological basis of vulnerability to several psychopathologies in which the dopaminergic system is involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 57 publications
(71 reference statements)
5
39
0
Order By: Relevance
“…Moreover, rats classified according to SIP acquisition as high drinkers (HD) and low drinkers (LD) manifest differences in pharmacological challenge with dopaminergic drugs. SIP was reduced in HD animals with 0.5 mg/kg of D-amphetamine and 10 mg/kg of cocaine, while in LD rats, SIP was reduced only at the higher dose of 2 mg/kg of Damphetamine (López-Grancha et al 2008). Thus, consistent with human data on inhibitory response control in the stop task previously mentioned (de Wit et al 2007), D-amphetamine effectively reduced the compulsive drinking in HD, perhaps by improving response inhibitory control over stopping an action.…”
Section: Individual Differences In Sip: Identification Of Compulsive mentioning
confidence: 70%
“…Moreover, rats classified according to SIP acquisition as high drinkers (HD) and low drinkers (LD) manifest differences in pharmacological challenge with dopaminergic drugs. SIP was reduced in HD animals with 0.5 mg/kg of D-amphetamine and 10 mg/kg of cocaine, while in LD rats, SIP was reduced only at the higher dose of 2 mg/kg of Damphetamine (López-Grancha et al 2008). Thus, consistent with human data on inhibitory response control in the stop task previously mentioned (de Wit et al 2007), D-amphetamine effectively reduced the compulsive drinking in HD, perhaps by improving response inhibitory control over stopping an action.…”
Section: Individual Differences In Sip: Identification Of Compulsive mentioning
confidence: 70%
“…Water bottles containing 100-ml fresh water were provided immediately before each session. The following measures were recorded for each rat: (a) total amount of water (ml) removed from the bottle, (b) total number of licks, and (c) and total number of nose-pokes (see López-Grancha et al, 2008, for more details).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the apparatus has been provided previously for SIP and delay-discounting task (Cardona et al, 2006;López-Grancha et al, 2008). The same chambers were also used in the 5-CSRT task, with an array of five contiguous square holes (2.5 cm), 2.2-cm deep and 2 cm above floor level at the back panel.…”
Section: Apparatus: Operant Chambersmentioning
confidence: 99%
See 1 more Smart Citation
“…All drugs were prepared to produce a total injection volume of 1.0 ml/kg and were injected intraperitoneally (i.p.). The AMPH doses used in this study have been previously shown to disrupt SIP (Liu et al 2005;López-Grancha et al 2008). The L-NAME dose used to antagonize the AMPH-induced behaviors in rats varies across a wide range in different experimental paradigms (Afanas'ev et al 2000;Przegaliński and Filip 1997;Przewłocka et al 1996;Stewart et al 1994).…”
Section: Sip Training Proceduresmentioning
confidence: 97%